The Impact of Leadership, Organizational Culture, and Organizational Climate on Employee Job Satisfaction - Rosari, Diana; Tjahjadi, Karel (E-Jurnal Manajemen Trisakti School of Management (TSM), 2023)
This study aims to determine whether there is an effect between leadership, organizational culture, and organizational climate on employee job satisfaction at KPP Madya Dua Jakarta Utara. The design of this research used in this research is explanatory and causal. The samples used in this research are 57 employees of KPP Madya Dua Jakarta Utara. The sampling method used in this study is a purposive sample and the data analysis method used multiple linear regression analysis. Research data is primary data collected by distributing questionnaires and using the Likert scale. Based on the results of the study, this research showed leadership has an effect on employee job satisfaction; organizational culture has an effect on employee job satisfaction; organizational climate has a positive effect on employee job satisfaction.